LncRNA CAIF inhibits autophagy and attenuates myocardial infarction by blocking p53-mediated myocardin transcription - Cui-Yun Liu (Nature Portfolio, 2018)
Little is known about the role of long lncRNAs in autophagy. The authors identify lncCAIF, and show that it suppresses cardiac autophagy and attenuates myocardial infarction by targeting p53 -mediated transcription of myocardin.